Техникалық оқу орындарында мамандарңды дайындауда кәсіптік білімнің орны - Еркетаев, Е.С.; Абенова, М.Б.; Жантулина, Д.З. (My University, 2013)
Nowadays teachers of Higher education institutions are demanded not only high profes- sional knowledge and skills, but also knowledge of pedagogy. So at present time in the educational environment of the Republic of Kazakhstan was formed direction connecting in the professional activity of teachers’ knowledge, which include educational technologies. Knowledge of new educational technologies and their application requires from teacher skills in using instructional technologies.